Evidence-based medicine, "placebos" and the homeopathy controversy - Turner, Andrew James (2012)
Homeopathic treatment has been available on the UK’s National Health Service (NHS) since 1948. In recent years the continued provision of homeopathy through the NHS has been increasingly questioned as part of the ascendency of evidence-based medicine (EBM). Indeed, in 2009 the House of Common’s Science and Technology committee commenced an ‘Evidence Check’ inquiry into Government policy supporting the NHS provision of homeopathic treatments. The controversy over whether homeopathic treatments ‘really’ work and whether they should be available through the NHS has generated much debate: at the heart of the controversy are questions about the nature of evidence in medicine, the validity of randomised trials and the nature and utility of ‘placebo effects’. Critics of homeopathy put forward the simple argument that best available evidence shows homeopathic treatments to be equivalent to placebo, and therefore conclude that it should not be available through publically funded healthcare.